School-based Streptococcal A Sore-throat Treatment Programs and Acute Rheumatic Fever Amongst Indigenous Māori: A Retrospective Cohort Study. Issue 11 (November 2020) - Walsh, Liam; Innes-Smith, Sandra; Wright, Janine; Michniewicz, Thanjon; Tozer, Megan; Humby, Jonathan; Ngata, Richard; Lennon, Diana; Scott-Jones, Joseph; Malcolm, John
Abstract : Background: Acute rheumatic fever (ARF) predominantly affects indigenous Māori schoolchildren in Bay of Plenty region, and more so male Māori students, especially when socioeconomically deprived. We evaluated the effectiveness of strategies for reducing ARF with group A streptococcal pharyngitis treatment in 2011–18. Methods: We retrospectively assessed outcomes of 3 open cohorts of Māori schoolchildren receiving different interventions: Eastern Bay rural Cohort 1, mean deprivation decile 9.80, received school-based sore-throat programs with nurse and general practice (GP) support; Eastern Whakatane township/surrounds Cohort 2, mean deprivation 7.25, GP management; Western Bay Cohort 3, mean deprivation 5.98, received predominantly GP care, but 3 highest-risk schools received school-based programs. Cases were identified from ICD10 ARF-coded hospital discharges, notifications to Ministry of Health, and a secondary-prevention penicillin database. Primary outcomes were first-presentation ARF cohorts' incidence preintervention (2000–10) and postintervention (2011–18) with cases over annual school rolls' Māori students-year denominators. Results: Overall, ARF in Maori schoolchildren declined in the cohorts with school-based programs. Cohort 1 saw a postintervention (2011–18) decline of 60%, 148 to 59/100, 000/year, rate ratio (RR) = 0.40(CI 0.22–0.73) P = 0.002. Males' incidence declined 190 to 78 × 100, 000/year RR = 0.41(CI 0.19–0.85) P = 0.013 and females too, narrowing gender disparities. Cohort 3 ARF incidence decreased 48%, 50 to 26/100, 000/year RR = 0.52(CI 0.27–0.99) P = 0.044. In contrast, ARF doubled in Cohort 2 students with GP-only care without school-based programs increasing 30 to 69/100, 000/year RR = 2.28(CI 0.99–5.27) P = 0.047, especially for males 39/100, 000/year to 107/100, 000/year RR = 2.71(CI 1.00–7.33) P = 0.0405. Conclusions: School-based programs with indigenous Māori health workers' sore-throat swabbing and GP/Nurse support reduced first-presentation ARF incidence in Māori students in highest-risk settings. Abstract : Supplemental Digital Content is available in the text.